Sex differences in distribution, management and outcomes of combined ischemic-bleeding risk following acute coronary syndrome. (15th April 2021) - Mohamed, Mohamed O.; Rashid, Muhammad; Timmis, Adam; Clarke, Sarah; Lawson, Claire; Michos, Erin D.; Kwok, Chun Shing; De Belder, Mark; Valgimigli, Marco; Mamas, Mamas A.
Abstract: Background: Risk factors for further bleeding and ischemic events after acute coronary syndrome (ACS) often overlap. Little is known about sex-based differences in the management and outcomes of ACS patients according to their combined bleeding-ischemic risk. Methods: All ACS hospitalizations in the United Kingdom (2010–2017) were retrospectively analyzed, stratified by sex and bleeding-ischemic risk combination (using CRUSADE and GRACE scores). Multivariable logistic regression was performed to examine association between risk-groups and 1) receipt of guideline-recommended management and 2) in-hospital outcomes. Results: Of 584, 360 patients, a third of males (32.3%) and females (32.6%) were in the dual high-risk group (High CRUSADE- High GRACE). In comparison to the dual low-risk group (Low CRUSADE-Low GRACE), the dual high-risk patients of both sexes were 59–83% less likely to receive inpatient revascularisation (PCI or CABG) and 50% less likely to receive dual antiplatelet therapy (DAPT) on discharge, with a significant increase in odds of MACE (~8 to 9-fold), all-cause and cardiac mortality (25 to 35-fold), and bleeding (78–91%). The greatest difference in management and clinical outcomes between sexes was found in the dual-high risk group where females were less likely to receive guideline-recommended therapy (revascularisation and DAPT), compared to males, and were more likely to experience MACE, all-cause and cardiac mortality. Conclusion: ACS patients with dual high-risk for bleeding and recurrent ischemia, especially females, are less likely to receive guideline-recommended therapy and experience significantly worse outcomes. Novel strategies are needed to effectively manage this highly prevalent, complex patient group and address the under-treatment of females. Graphical abstract: Summary of Study Findings Unlabelled Image Highlights: First nationwide study to examine receipt of guideline-recommended therapy for ACS according to sex and dual bleeding-ischemic risk group One in three males and females are at a dual high-risk of bleeding and ischemia Females are less likely to receive guideline-recommended therapy and experience significantly worse outcomes. A gap in evidence remains regarding optimal strategies for this dual high-risk group, especially among females who experience worse outcomes.